Antidysbiotic prophylaxis and therapy of non-infectious colitis - Bocharov, A. V. (Journal of Education, Health and Sport, 2019)
The increasing incidence of dysbiosis and its pathogenic consequences naturally raises questions about the search for treatment and prevention. It is established that in the pathogenesis of non-infectious colitis the decisive role is played by dysbiosis, that is, the reduction of the level of probiotic bacteria and the increase in the number of conditionally pathogenic species, especially their virulent strains. Under the conditions of functioning of the normal microbial composition of the microbiome, the probiotic bacteria exert a suppressive effect on the conditionally pathogenic microflora. It is important that even with the development of dysbiosis only the ratio of the two groups of microorganisms changes, and, for example, the biotic bacteria do not completely disappear, which makes it possible to restore them. The results of many years of experimental studies carried out in the laboratory of Professor AP Levitsky showed the antidysbiotic property of polyphenolic compounds, in particular bioflavonoids. It is known that bioflavonoids belong to plant substances and have a very wide range of biological effects: antioxidant, anti-enzyme, membrane-protecting, hepatoprotective, anti-dysbiotic, anti-inflammatory and therefore used for the treatment of many diseases, in the first place.